La formazione imprenditoriale in liguria: opinioni a confronto. Il punto di vista degli attori istituzionali 2 Global - Testa, Stefania; Frascheri, Silvana (Piccola Impresa / Small Business, 2011)
Notwithstanding the largely shared view on the importance of entrepreneurship education and training, or maybe also for this reason, a plethora of definitions and goals have been developed, resulting in an ambiguity in the term. The aim of this paper is to investigate the different perspectives on EE&T held by the stakeholders involved in these initiatives at local level, highlighting the points of major contrast together with similarities in order to provide new insights into the topic. Perspectives have been collected by means of a qualitative research. The paper is organized as follows: first, literature about EE&T is briefly reviewed. Second, the research setting is described. Third, the methodology is introduced. Fourth, the results are discussed. Finally, some conclusions are provided.